Analisis Perlindungan Kerja Terhadap Kinerja Pekerja Migran Indonesia Melalui Mediasi Penempatan Kerja (Studi Kasus Dinas Ketenagakerjaan Kota Medan) - PRETTY LUCI LUMBANRAJA (SMART Management Journal, 2021)
Professional workers are workers who are able to produce good performance. Good employee performance in an organization leads to the achievement of good income for the workers themselves. This can increase the national income of the country. The low income of people in a country, encourages them to go across national borders to become Indonesian Migrant Workers in other countries. In addition, the policy issued by the government regarding the placement of PMI abroad has also become a solution to domestic economic problems. namely reducing unemployment. This study uses quantitative methods, by conducting questionnaires, interviews and observations on PMI from Medan who departed for Malaysia. Hypothesis testing using SEM analysis at a confidence level of 95% (α = 0.05) to 100 research respondents. The results of this study are that there is a positive and significant effect of job protection on job placement, there is a positive and significant effect of job placement on the performance of Indonesian migrant workers and there is a positive and significant effect of job protection on the performance of migrant workers through job placement as an intervening variable.